(Pentamethylcyclopentadienyl)cobalt(III)‐Catalyzed Direct Trifluoromethylthiolation of Arenes via C−H Activation. Issue 11 (15th March 2017) - Liu, Xu‐Ge; Li, Qingjiang; Wang, Honggen
Abstract: The direct trifluoromethylthiolation of arenes was realized via (pentamethylcyclopentadienyl)cobalt(III)‐catalyzed C(sp 2 )‐H activation and coupling with AgSCF3 under the assistance of a directing group. The reaction features redox‐neutrality, mild conditions, broad substrate scope, and good functional group tolerance. Preliminary mechanistic studies have been conducted. Abstract :